Enhancing Conceptual Understanding and Learning Interest in Geometry through Augmented Reality-Based Learning Media - Asmaul Husna; Irma Risdiyanti; Yufitri Yanto; Ida Hamidah; Rhomiy Handican; Ahmad Yani (JDIME: Journal of Development and Innovation in Mathematics Education, 2025)
This study aims to develop Augmented Reality (AR)-based learning media in geometry courses to enhance students' conceptual understanding and learning interest. This research uses a Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) for media development procedures. The subjects of the study involved students from the Mathematics Education program at a university in Indonesia. Data were collected through validation sheets and effectiveness tests, with validity and reliability tested using paired sample t-tests. The results showed that the AR-based learning media developed received an excellent validation score (4.2/5) from experts and demonstrated significant effectiveness in improving conceptual understanding of geometry (t = 15.23, p < 0.05) as well as students' learning interest (t = 12.76, p < 0.05). The use of AR in geometry learning was found to increase student engagement and make abstract concepts easier to understand. These findings are consistent with previous studies showing that AR can enhance the quality of learning, particularly in complex subjects such as geometry. This study provides empirical evidence regarding the potential of AR in higher education and suggests broader implementation across various disciplines to improve students' understanding and motivation.